Rénovation de deux structures scolaires, au Danemark : Quelles évolutions, quelles perspectives pédagogiques ? - France Roy (Éducation et Socialisation)
This article discusses the case of two schools, that are “famous”, each in her own way in Denmark, which recently received ambitious expansion and renovation programs : Rødding Højskole (Rødding Folkhighschool) and Munkegaardsskolen (Munkegaard’s school). These projects are part of the history of these schools, of the country, and are based on a child’s or man’s conception specifically developed in the Nordic countries. They show a need to adapt buildings to technical developments and constraints, and a wish to improve education and teaching methods. Our article reports, for part, of the architectural evolution of these two schools, each understood in historical, social and educational context ; then we make a comparison of the two projects and of their foundations, and we open research perspectives on the pedagogical contribution that these architectural evolutions could induce.